Quantitative and Qualitative Analysis of Bone Marrow CD8+ T Cells from Different Bones Uncovers a Major Contribution of the Bone Marrow in the Vertebrae - Geerman, Sulima; Hickson, Sarah; Brasser, Giso; Pascutti, Maria Fernanda; Nolte, Martijn A. (Frontiers in Immunology, 2016)
Bone marrow (BM) plays an important role in the long-term maintenance of memory T cells. Yet, BM is found in numerous bones throughout the body, which are not equal in structure, as they differ in their ratio of cortical and trabecular bone. This implies, that BM cells within different bones are subjected to different microenvironments, possibly leading to differences in their frequencies and function. To address this, we examined BM from murine tibia, femur, pelvis, sternum, radius, humerus, calvarium and the vertebrae and analyzed the presence of effector memory (TEM), central memory (TCM) and naïve (TNV) CD8+ T cells. During steady state conditions, the frequency of the total CD8+ T cell population was comparable between all bones. Interestingly, most CD8+ T cells were located in the vertebrae, as it contained the highest amount of BM cells. Furthermore, the frequencies of TEM, TCM and TNV cells were similar between all bones, with a majority of TNV cells. Additionally, CD8+ T cells collected from different bones similarly expressed the key survival receptors IL-7Rα and IL-15Rβ. We also examined BM for memory CD8+ T cells with a tissue-resident memory phenotype, and observed that approximately half of all TEM cells expressed the retention marker CD69. Remarkably, in the memory phase of acute infection with the lymphocytic choriomeningitis virus (LCMV), we found a massive compositional change in the BM CD8+ T cell population, as the TEM cells became the dominant subset at the cost of TNV cells. Analysis of Ki-67 expression established that these TEM cells were in a quiescent state. Finally, we detected higher frequencies of LCMV-specific CD8+ T cells in BM compared to spleen and found that BM in its entirety contained five-fold more LCMV-specific CD8+ T cells. In conclusion, although infection with LCMV caused a dramatic change in the BM CD8+ T cell population, this did not result in noticeable differences between BM collected from different bones. Our findings suggest that in respect to CD8+ T cells, BM harvested from a single bone is a fair reflection of the rest of the BM present in the murine body.